2008
DOI: 10.1111/j.1525-139x.2008.00451.x
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Transposed Brachiobasilic Fistulae with Nontransposed Fistulae and Grafts in the Fistula First Era

Abstract: This retrospective study compares outcomes of transposed brachiobasilic fistulae (avf), nontransposed avf, and grafts (avg). There were 161 (21%) transposed avf, 321 (42%) nontransposed avf, and 285 (37%) avg placed and followed over a 3-year period. Of the nontransposed avf, 203 (63%) were forearm radiocephalic avf and 118 (37%) were upper arm brachiocephalic avf. Grafts were able to be used in shorter time than avf and had a lower primary failure rate. However, avg had a significantly higher infection rate (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
39
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 22 publications
(25 reference statements)
7
39
0
Order By: Relevance
“…Several studies have compared various BBAVF with AVG. 3,[11][12][13][14][15][16][17][18][19] In particular, if the patient is already undergoing dialysis via a central venous permacath, one must weigh the risks of prolonged central vein catheterization while awaiting BBAVF maturation with the increased complication rate associated with AVG placement. A previous study showed an increased rate of thrombosis with AV graft compared with BBAVF (relative risk, 2.6; 95% CI, 1.3-5.3).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have compared various BBAVF with AVG. 3,[11][12][13][14][15][16][17][18][19] In particular, if the patient is already undergoing dialysis via a central venous permacath, one must weigh the risks of prolonged central vein catheterization while awaiting BBAVF maturation with the increased complication rate associated with AVG placement. A previous study showed an increased rate of thrombosis with AV graft compared with BBAVF (relative risk, 2.6; 95% CI, 1.3-5.3).…”
Section: Discussionmentioning
confidence: 99%
“…Fistula prevalence also increased from 33% in 2003 to 41% in 2005 1. Patients with end-stage renal failure need to receive hemodialysis through an effective arteriovenous fistula (AVF) until renal transplantation.…”
Section: Introductionmentioning
confidence: 99%
“…However, the early thrombosis rate of the BB AVGs in our series was 24.3% (10/41), which was higher than the reported 6.7 to 15.7% [5, 15]. We attempted to explore if the graft material played a role in early AVG thrombosis.…”
Section: Discussionmentioning
confidence: 55%
“…Current recommendations are for either an autogenous BBTAVF or a forearm loop BB AVG. Several studies have favoured the BBTAVF over the forearm loop BB AVG procedure on the basis of better patency rates and fewer interventions [5, 6, 15]. However, these studies report only the outcomes from accesses that were successful initially and primary failure cases were excluded from the analysis.…”
Section: Discussionmentioning
confidence: 99%